Comparison of Phenolic Compounds and Antioxidant Activities of Raw and Cooked Turkish Artichoke Cultivars - Kayahan, Seda; Saloglu, Didem (Frontiers in Sustainable Food Systems, 2021)
The objective of this work was to determine total phenolic compounds and antioxidants in raw and cooked Sakiz and Bayrampasa variety artichokes in parts such as inner bracts, stems, receptacles, and outer bracts. The artichokes were cooked by boiling, microwaving, and baking methods and total phenolic compounds and antioxidants of cooked artichokes were evaluated. While TPC, DPPH, and CUPRAC values for the leaves of raw Bayrampasa artichoke were found to be 686 mg GAE/100 g, 478 mg TE/100 g, and 4875 mg TE/100 g, respectively, TPC, DPPH, and CUPRAC values for stems of Sakiz artichoke were determined to be 1579 mg GAE/100 g, 1259 mg TE/100 g, and 3575 mg TE/100 g. A significant increase in the content of TPC, DPPH, and CUPRAC values was observed for all cooking applications of both artichokes. DPPH and CUPRAC values increased by 11 and 43 times and 17 and 6.7 times after baking of Sakiz and microwave cooking of Bayrampasa, respectively. Chlorogenic acid, cynarine, and cynaroside content of both artichokes had an increment after all cooking applications. Chlorogenic acid content was improved 29 and 58 times after baking of Sakiz and microwave cooking of Bayrampasa, respectively.